1999
DOI: 10.1038/sj.bjc.6690522
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus infection in patients with lymphoproliferative disorders in Southern Turkey

Abstract: Anti-hepatitis C virus (HCV) antibody prevalence was investigated in 228 patients with lymphoproliferative disorders (LPDs). Twenty-six of 228 (11.40%) patients with LPDs were positive for anti-HCV which was higher than the donor population ( P = 0.0007). Nine of 98 cases with non-Hodgkin's lymphoma, five of 47 cases with multiple myeloma, seven of 36 cases with Hodgkin's disease, four of 38 cases with chronic lymphocytic leukaemia and one of nine cases with acute lymphoblastic leukaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2003
2003
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
2
24
0
1
Order By: Relevance
“…In these studies, HCV prevalence was compared either with a donor population or with other nonmalignant diseases or nonlymphoid malignancies. In our previous study, the prevalence of anti-HCV was 9.18% [41]. In the present study, anti-HCV was found in 8.1% of the cases.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…In these studies, HCV prevalence was compared either with a donor population or with other nonmalignant diseases or nonlymphoid malignancies. In our previous study, the prevalence of anti-HCV was 9.18% [41]. In the present study, anti-HCV was found in 8.1% of the cases.…”
Section: Resultssupporting
confidence: 58%
“…The prevalence of HCV in NHLs and/or LPDs has been found to be between 0-38% [17,18,21,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. As seen in these series, prevalence was the highest in Italy, the USA, and Japan, and lowest in England and France.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The first studies came from Italy, and studies from France, Japan, the United States, and England followed. HCV prevalence in these series was between 0.004% and 33% [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The lowest prevalence was found in a British study, where 1 out of 268 lymphoma patients had tumors positive for HCV.…”
Section: Discussionmentioning
confidence: 99%
“…OR for anti-HCV was 24.09. 2 In our second study, anti-HCV antibody was examined in 223 cases with NHL and it was found to be positive in 18 (8.1%). Common OR was 34.56 and corrected OR was 19.07.…”
mentioning
confidence: 94%